Perencanaan Struktur Gedung Perkantoran 4 LantaiDengan Sistem Rangka Pemikul Momen Menengah(SRPMM) Di Wilayah Sukoharjo - Noviyanti, Ika; , Ir.Aliem Sudjatmiko, M.T (2016)
Sukoharjo regency is part of Solo Raya region that has a lot of potential to improve the welfare of people in agriculture, tourism, and industry. Construction of office buildings into one option to support the activities of the industry and provide comfort for occupants by utilizing the available land. Therefore, it will be planned 4 floors with Intermediate Moment Resisting Frame (IMRF). Planning a office building refers to the regulations (SNI) has published the latest government, namely SNI 1726 - 2012 (the rules of building structure earthquake for building structure and non structure). Planning a office building includes roof slabs, slabs, columns, beams, foundations and sloof. The location building in Sukoharjo (latitude -7,602 longitude 110,810) and soil site clasification is SD (intermediate soil), earthquake resistant building with the response modification factor (R) amounted to 5, the primary factor building Ie with a value of 1,0. Concrete quality used f'c = 25 MPa, steel reinforcement for longitudinal bars fy = 400 MPa, shear bars fyt = 300 MPa and 320 MPa for roof slabs, slabs. The results of planning for roof slabs with a thickness 10 cm and a slab with 12 cm, beam structure with dimensions 200/400 mm. As for column using with dimensions of 450/450 mm. For bottom structure using pile foundations depth of -16 m with poer dimensions of 2,5 x 2,5 m.